The benefits of edible mushroom polysaccharides for health and their influence on gut microbiota: a review - Zhao, Qilong; Jiang, Yu; Zhao, Qian; Patrick Manzi, Habasi; Su, Li; Liu, Diru; Huang, Xiaodan; Long, Danfeng; Tang, Zhenchuang; Zhang, Ying (Frontiers in Nutrition, 2023)
The gut microbiome is a complex biological community that profoundly affects various aspects of human health, including dietary intake, disease progression, drug metabolism, and immune system regulation. Edible mushroom polysaccharides (EMPs) are bioactive fibers derived from mushrooms that possess a range of beneficial properties, including anti-tumor, antioxidant, antiviral, hypoglycemic, and immunomodulatory effects. Studies have demonstrated that EMPs are resistant to human digestive enzymes and serve as a crucial source of energy for the gut microbiome, promoting the growth of beneficial bacteria. EMPs also positively impact human health by modulating the composition of the gut microbiome. This review discusses the extraction and purification processes of EMPs, their potential to improve health conditions by regulating the composition of the gut microbiome, and their application prospects. Furthermore, this paper provides valuable guidance and recommendations for future studies on disease management.